Nghiên cứu một số yếu tố ảnh hưởng đến quá trình tổng hợp vật liệu rây phân tử mao quản trung bình SBA-16 từ nguồn silic điều chế từ vỏ trấu. - Thắng, Hồ Sỹ; Khiếu, Đinh Quang; Hoà, Trần Thái; Phú, Nguyễn Hữu (Vietnam Journal of Chemistry, 2012)
The synsthesis of SBA-16 silica molecular sieve using block copolymer EO106PO70EO106 (F127) as structure-directing-agent, SiO2 prepared from rice husk as silica source and using copolymer blends was investigated. Three series of samples were prepared to study the change trend of mesoporous structure by the variations of ratios of butanol/SiO2, HCl/SiO2 and P123/F127. The resulting SBA-16 materials were characterized by TG-DSC, XRD, N2 physical sorption isotherms. The experiments show that butanol/SiO2, HCl/SiO2 in the range of 0.98-2.45; 2.12-2.47, respectively could provide a highly ordered mesoporous material with high surface areas. The pore size of SBA-16 could be varied by using copolymer blends of P123 and F127.